2021
DOI: 10.1186/s40658-021-00384-5
|View full text |Cite
|
Sign up to set email alerts
|

Human biodistribution and dosimetry of [11C]-UCB-J, a PET radiotracer for imaging synaptic density

Abstract: Rationale [11C]-UCB-J is an emerging tool for the noninvasive measurement of synaptic vesicle density in vivo. Here, we report human biodistribution and dosimetry estimates derived from sequential whole-body PET using two versions of the OLINDA dosimetry program. Methods Sequential whole-body PET scans were performed in 3 healthy subjects for 2 h after injection of 254 ± 77 MBq [11C]-UCB-J. Volumes of interest were drawn over relevant source organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Advances in structural and functional connectivity imaging techniques, developed during studies on the brains of living animal models and patients, have enabled the transition from clinical signs and symptoms-based AD diagnosis to a biomarkers-based diagnosis. This transition has promoted a multimodal approach to the study of AD that has increased the prediction of AD incidence and staging by combining the results of high-resolution structural and volumetric MRI, diffusion tensor imaging and fibre tractography MRI, fMRI, FDG-PET, PET imaging with radiotracers for brain synaptic density quantification, quantitative EEG, and body fluid sampling for synaptic protein markers, soluble Aβ peptides and tau [11,17,20,66,[199][200][201][202]204,205,223,234,236,[238][239][240][241][250][251][252][253][254][255].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in structural and functional connectivity imaging techniques, developed during studies on the brains of living animal models and patients, have enabled the transition from clinical signs and symptoms-based AD diagnosis to a biomarkers-based diagnosis. This transition has promoted a multimodal approach to the study of AD that has increased the prediction of AD incidence and staging by combining the results of high-resolution structural and volumetric MRI, diffusion tensor imaging and fibre tractography MRI, fMRI, FDG-PET, PET imaging with radiotracers for brain synaptic density quantification, quantitative EEG, and body fluid sampling for synaptic protein markers, soluble Aβ peptides and tau [11,17,20,66,[199][200][201][202]204,205,223,234,236,[238][239][240][241][250][251][252][253][254][255].…”
Section: Discussionmentioning
confidence: 99%
“…Human biodistribution and dosimetry estimates were calculated with OLINDA software from the data of three healthy subjects injected with the [11C]UCB-J PET radiotracer and subjected to sequential whole-body PET scans for two hours. The study concluded that a single intravenous administered dose of [11C]UCB-J enables multiple PET examinations to be carried out on the same subject without exceeding the annual dose limitations [254].…”
Section: Evaluations Of Pet Radiotracers For Brain Synaptic Density Q...mentioning
confidence: 99%
“…The outcome is similar to the study for the dosimetry calculation of [ 18 F]MK-6240, where the calculated effective doses by both versions of the OLINDA/EXM displayed no significant difference (Koole et al 2020 ; Ohnishi et al 2023 ). Compared to OLINDA/EXM v.1.1, the version of v.2.1 added the choice of the newer phantom, updated special models, and the modified reports of dose factor and tissue weighting factor (Cawthorne et al 2021 ). Rather than the phantom used in v.1.1, the newer phantom based on ICRP89 is gender-specific and the modified organ mass provides more accurate anatomic information (Valentin 2002 ).…”
Section: Discussionmentioning
confidence: 99%